Flourshing Pada Womenpreneur di Daerah Istimewa Yogyakarta - Rusyda Nurul Fajri Daulay; Purwadi; Nina Zulida Situmorang (Psyche 165 Journal, 2021)
Every individual has the potential to achieve flourish, including mompreneurs in order to achieve a good life by optimizing their drastic potential. Based on this, it aims to determine the flourshing women preneuer and the aspects forming the flourishing women preneuer in the Special Region of Yogyakarta.Qualitative method with a phenomenological approach, interview data collection techniques were carried out on 6 womenpreneuer subjects. Triangulation was carried out by interviewing the subject's closest person. The sampling technique used purposive sampling. The results show that the six subjects have flourished by showing the five aspects of PERMA, namely positive emotion, engagement, positive relationship, meaning of life, accomplishment in their life.